Autophagy promotes hepatic cystogenesis in polycystic liver disease by depletion of cholangiocyte ciliogenic proteins. Issue 5 (8th February 2022) - Masyuk, Anatoliy I.; Masyuk, Tatyana V.; Trussoni, Christy E.; Pirius, Nicholas E.; LaRusso, Nicholas F.
Abstract: Backgrounds and Aims: Polycystic liver disease (PLD) is characterized by defective cholangiocyte cilia that regulate progressive growth of hepatic cysts. Because formation of primary cilia is influenced by autophagy through degradation of proteins involved in ciliogenesis, we hypothesized that ciliary defects in PLD cholangiocytes (PLDCs) originate from autophagy‐mediated depletion of ciliogenic proteins ADP‐ribosylation factor‐like protein 3 (ARL3) and ADP‐ribosylation factor‐like protein 13B (ARL13B) and ARL‐dependent mislocation of a ciliary‐localized bile acid receptor, Takeda G‐protein‐coupled receptor 5 (TGR5), the activation of which enhances hepatic cystogenesis (HCG). The aims here were to determine whether: (1) ciliogenesis is impaired in PLDC, is associated with increased autophagy, and involves autophagy‐mediated depletion of ARL3 and ARL13B; (2) depletion of ARL3 and ARL13B in PLDC cilia impacts ciliary localization of TGR5; and (3) pharmacological inhibition of autophagy re‐establishes cholangiocyte cilia and ciliary localization of ARL3, ARL3B, and TGR5 and reduces HCG. Approach and Results: By using liver tissue from healthy persons and patients with PLD, in vitro and in vivo models of PLD, and in vitro models of ciliogenesis, we demonstrated that, in PLDCs: ciliogenesis is impaired; autophagy is enhanced; ARL3 and ARL13B are ubiquitinated by HDAC6, depleted in cilia, and present in autophagosomes; depletion of ARL3 and ARL13B impacts ciliary localization of TGR5; and pharmacological inhibition of autophagy with mefloquine and verteporfin re‐establishes cholangiocyte cilia and ciliary localization of ARL3, ARL13B, and TGR5 and reduces HCG. Conclusions: The intersection between autophagy, defective cholangiocyte cilia, and enhanced HCG contributes to PLD progression and can be considered a target for therapeutic interventions. Abstract : image